Persentase Edible Offal Babi Nias Jantan Pada Berbagai Umur Ternak - Salam N. Aritonang (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The research of edible offal percentage of male Nias pig in several animal ages has been carried out on ninety male Nias pig, which consisted of five aged group: A (<269 days old), B (270-298 days old), C (299-327 days old), D (328-356 days old) and E (> 357days old). The research was done by measuring of body and edible offal weight, edible offal percentage through out in the slaughter house in Gunungsitoli Nias. The relationship between animal age and each parameter measured were calculated by using regression analysis. The result of research indicated that there was a close relationship between animal age with their edible offal percentage. Increase of pig age were followed by decreasing of offal percentage with correlation coefficients of 0.896.